Clinical outcomes and metastatic behavior between de novo versus recurrent HER2-positive metastatic breast cancer: A 17-year single-institution cohort study at Taipei Veterans General Hospital. Issue 1 (6th January 2022) - Cheng, Han-Fang; Tsai, Yi-Fang; Huang, Chi-Cheng; Lien, Pei-Ju; Wang, Yu-Ling; Hsu, Chih-Yi; Chen, Yen-Jen; Liu, Chun-Yu; Chao, Ta-Chung; Lin, Yen-Shu; Feng, Chin-Jung; Chiu, Jen-Hwey; et al.
Abstract : Background: To assess the clinical outcomes and metastatic behavior between de novo versus recurrent human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (MBC) based on a single-institution database in Taiwan. Methods: We retrospectively identified patients diagnosed between January 2000 and December 2017 with de novo stage IV or recurrent HER2-positive MBC. Several variables were recorded in patients with recurrent disease: age at diagnosis, metastatic site, hormone receptor (HR) status, HER2 status, and disease-free interval (DFI). Treatments and metastatic patterns were compared between de novo stage IV and recurrent MBC cohorts. Post-metastasis survival (PMS) was estimated using the Kaplan-Meier method with log-rank tests. Hazard ratios and 95% CIs were estimated using Cox regression analysis. Results: In total, 1360 patients were diagnosed with breast cancer with HER2 overexpression. At baseline, de novo stage IV patients were older than recurrent MBC patients (median age 58 vs 53). The majority of the de novo stage IV patients were diagnosed after 2010, while most of the recurrent MBC patients were diagnosed during 2000-2009. An increased number of de novo stage IV patients underwent targeted therapy than recurrent MBC patients was also noted. PMS in patients with de novo stage IV and recurrent MBC was 79.2 months and 61.8 months, respectively, which indicated significant better survival in de novo stage IV than those with recurrent MBC disease. Longer survival was also noted in de novo stage IV and recurrent MBC with DFI >24 months than in those with recurrent MBC with DFI <24 months and in patients receiving HER2-targeted therapy after MBC diagnosis than in those not receiving the therapy. However, median PMS showed no significant difference between patients with the luminal B2 (HR-positive, HER2-negative) and HER2-enriched (HR-negative, HER2-positive) subtypes. After adjustment in multivariate analysis, a low risk of BC-specific death was observed in patients aged >50 years, those receiving HER2-targeted therapy for MBC, and those with oligometastasis, while patients with first metastases to the liver or brain showed a higher risk of BC-specific death than those without metastases. Conclusion: De novo and recurrent MBC have distinct characteristic, metastatic patterns and outcomes in Asian HER2-positive breast cancer patients. The age distribution and survivals between HR+/– status were different to non-Asian group. These differences should be further investigated in the future considering ethnic factor.